Improvement of Water Softening Method for Cooling Systems of Locomotives of Railway Depots - Javohir, Ozodjonov; Javlon, Alimukhamedov; Askar, Babayev; N. N., Tukhtarov (International Journal on Orange Technologies, 2023)
Ensuring the needs of all sectors of the national economy with clean drinking water in sufficient quantity and quality is given great importance and is considered one of the important issues. Information on water, technical composition and analysis of railway enterprises is presented.